Emerging polymeric biomaterials and manufacturing techniques in regenerative medicine. Issue 5 (16th February 2022) - Xia, Dan; Chen, Jiatian; Zhang, Zhongyang; Dong, Mingdong
Abstract: The current demand for patients' organ and tissue repair and regeneration is continually increasing, where autologous or allograft is the golden standard treatment in the clinic. However, due to the shortage of donors, mismatched size and modality, functional loss of the donor region, possible immune rejection, and so forth, the application of auto‐/allo‐grafts is frequently hindered in many cases. In order to solve these problems, artificial constructs structurally and functionally imitating the extracellular matrix have been developed as substitutes to promoting cell attachment, proliferation, and differentiation, and ultimately forming functional tissues or organs for better tissue regeneration. Particularly, polymeric materials have been widely utilized in regenerative medicine because of their ease of manufacturing, flexibility, biocompatibility, as well as good mechanical, chemical, and thermal properties. This review presents a comprehensive overview of a variety of polymeric materials, their fabrication methods as well applications in regenerative medicine. Finally, we discussed the future challenges and perspectives in the development and clinical transformation of polymeric biomaterials. Abstract : With the evolution of the times, the definition of the essential nature of biological materials has undergone a fundamental change from biocompatibility to biomimicry, a process, which is still ongoing. Due to ease of manufacturing, flexibility, biocompatibility, as well as good mechanical, chemical, and thermal properties, polymeric biomaterials are widely applied in regenerative medicine, including bone, cardiovascular, skin, verve, biomedical devices, and so forth.